2022
DOI: 10.1111/1750-3841.16168
|View full text |Cite
|
Sign up to set email alerts
|

Identification and confirmation of key compounds causing cooked off‐flavor in heat‐treated tomato juice

Abstract: Cooked off-flavor produced by heat treatment greatly limited the acceptability of commercial tomato juice. To screen and identify the cooked off-flavor compounds, gas chromatography-mass spectrometry-olfactometry (GC-MS-O), aroma extract dilution analysis (AEDA), gas chromatography-mass spectrometry (GC-MS), and odor activity value (OAV) calculation were applied simultaneously. The results showed that there were 17 aroma-active compounds in tomato juice samples. Among them, three newly formed sulfur-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…This aligns with the findings of Liu [53], who determined that (E)-2-nonenal plays a significant role in fruit aroma. The compounds dimethyl trisulfur, 2-octenal, (E)-, and furan, 2-pentyl-, which were identified in this study, have also been the subject of previous investigation [42,54,55]. It is noteworthy that this study has also identified two substances, namely 2-thiophenemethanethiol and pyrazine, 2-methoxy-3-(2-methylpropyl)-, which significantly contribute to the olfactory perception of tomato fruits.…”
Section: Discussionsupporting
confidence: 59%
“…This aligns with the findings of Liu [53], who determined that (E)-2-nonenal plays a significant role in fruit aroma. The compounds dimethyl trisulfur, 2-octenal, (E)-, and furan, 2-pentyl-, which were identified in this study, have also been the subject of previous investigation [42,54,55]. It is noteworthy that this study has also identified two substances, namely 2-thiophenemethanethiol and pyrazine, 2-methoxy-3-(2-methylpropyl)-, which significantly contribute to the olfactory perception of tomato fruits.…”
Section: Discussionsupporting
confidence: 59%
“…Salmorejo has a complex flavour chemistry, involving many non-oxidized and oxidized volatiles from tomato, vinegar, garlic, olive oil, and other ingredients generated during processing and further storage. Liu et al (2022) [12] studied the main aroma-active compounds of fresh and heat-treated (hot break of pulp and sterilisation at 90 • C for 15 min) tomato juice. In this study, different volatiles were associated with fresh (E-2-nonenal), grass (hexanal, 3-hexenal), fruity (6methyl-5-hepten-one and citral), floral (linalool, phenylacetaldehyde, and b-lonone), and cooked (dimethyl sulphide, dimethyl trisulphide, methional, and 1-octenone) odours.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, salmorejo cannot be elaborated with blanched tomato and must be carefully pasteurised as its sensory attributes are easily altered. Heating can bring some sensory changes, including the formation of cooked fruit flavour related to sulphur volatiles and others [12,13], discolouration due to the degradation of lycopene and other pigments [14], or an increase in consistency due to pectin transformations [15]. These changes lead to products acquiring the sensory characteristics of canned heated tomato, undesirable for minimally pasteurised products such as salmorejo, gazpacho, or grated fresh tomato.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, EH treatment could improve the content of flavour components in fermented jujube juice. [144] Tomato juice Identification and control of cooked flavour in heat-treated tomato juice.…”
Section: Lan Et Al (2021)mentioning
confidence: 99%